Avaliação da distribuição de pressão plantar e da estabilidade postural em mulheres jovens saudáveis e sua associação com parâmetros antropométricos - Cardoso, Patricia Pinho (2019)
INTRODUCTION:To maintain adequate postural stability is a challenge, and it becomes even more difficult in the female population. This is mainly due to several anatomical factors, such as breast enlargement and differencesin the pelvic region.Besides being an important risk factor for other chronic disease, excess adiposity can also have a profound impact on mobility and postural stability. It is important to evaluate the influence of excess weight on plantar pressures and their consequences during gait.OBJECTIVE:To determine the characteristics of plantar pressure and balance in young, healthy women and the association with variables that discriminate the increase in plantar pressure in this population.METHODS:This is a cross-sectional study, composed of 140 young, healthy women, aged 29,9±7,54 years. The participants were submitted to anthropometric assessment and bioimpedance, for measuring body adiposity.To assess the distribution of plantar pressure and balance, It was used baropodometry. A descriptive analysis of some variables was performed, in which the averages, standard deviations, median, 25th and 75th percentiles were calculated. To test the normality of the variables, the Kolmogov-Smirnoff test was used.To verify the association between anthropometric variables, the body adiposity indexes and baropodometric findings were used the Pearson Correlation and Spearman Correlation tests. The Receiver Operating Characteristic (ROC) curve was used to determine the cuttingpoints in which anthropometric variables begin to change plantar pressure values, considering a 95% confidence interval.RESULTS:A descriptive analysis of baropodometric and stabilometric values found in this population was performed. From BMI 25.4, of the fat percentage (%G) above 35,1% nd waist circumference (WC) greater than 80cm, plantar pressure values begin to undergo changes.It is possible to observe a significant difference between the eutrophic and overweight groups in the baropodometric variables,area and maximum pressure and in the stabilometric anteroposterior and laterolateral displacement.The overweight group presentedhigher plantar pressure values(p<0,01).CONCLUSION:Lower overweight ranges were associated with increased plantar pressure and worse postural stability in this population.